Musicoterapia y aromaterapia como herramienta de estimulación para niños con parálisis cerebral infantil de las aulas de inclusión en la unidad educativa Emaús de fe y alegría en el periodo 2017 – 2018 - Barragán Villavicencio, Magaly Anabel (2018)
This paper presents the sistematitation of a intervention proyect which objective was to apply music therapy and aromatherapy to kids with cerebral palsy (CP) that belong to the inclusion proyect at educational unit “Emaús”, this was accomplished by applying stimulation session that try to improve the cognitive, motor, language and social capability of the kids that were part of this proyect. The methodology used to accomplished the objectives of this investigation were qualitative and quantitative, this methods allows to evaluate the initial conditions of the group of kids that were part of this study, so that enable to develop a planification of wich kind of music therapy and aromatherapy sessions will be apply to improve their development. After the intervention project was apply, the results were evaluated through the implementation of a inquiry to the parents and teachers of the kids with CP, to determine if wherether or not the therapies were effective.